2003
DOI: 10.1016/s0304-3932(03)00083-7
|View full text |Cite
|
Sign up to set email alerts
|

Does the Barro–Gordon model explain the behavior of US inflation? A reexamination of the empirical evidence

Abstract: RÉSUMÉCe papier teste les prédictions du modèle de Barro-Gordon en utilisant les données américaines sur l'inflation et le chômage. Pour ce faire, il construit un modèle de jeu théorique général avec des préférences asymétriques qui englobe le modèle de Barro-Gordon et une version du modèle de Cukierman qui sont des cas spéciaux. Les tests du rapports de vraisemblance indiquent que la restriction imposée par le modèle de Barro-Gordon est rejetée par les données, mais celle imposée par la version du modèle de C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
81
1
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(92 citation statements)
references
References 19 publications
6
81
1
3
Order By: Relevance
“…By focusing on short term results, it is possible that the policy maker pursues policies which create surprise inflation. This inflation bias result has been explored in numerous empirical studies including Ireland (1999), Ruge-Murcia (2003, 2004 and others. Although Ruge-Murcia (2003, 2004 showed that the Barro and Gordon style inflation bias is not supported by the data, he did show that an inflation bias arising from asymmetric monetary authority preferences is.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…By focusing on short term results, it is possible that the policy maker pursues policies which create surprise inflation. This inflation bias result has been explored in numerous empirical studies including Ireland (1999), Ruge-Murcia (2003, 2004 and others. Although Ruge-Murcia (2003, 2004 showed that the Barro and Gordon style inflation bias is not supported by the data, he did show that an inflation bias arising from asymmetric monetary authority preferences is.…”
Section: Introductionmentioning
confidence: 92%
“…We show that for larger coefficient variation settings the mean value of the coefficient decreases. Although this implies that the mean value of the coefficient becomes statistically insignificant, it is important to stress that it does not imply that the asymmetric monetary planner preference hypothesis suggested in Ruge-Murcia (2003) is invalid because the time varying parameter is still tied to the conditional unemployment variance. What our results do show is that time variation could account for the range of parameter estimates tied to the conditional unemployment volatility found in the literature.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Our paper is also related to work by Ireland (1999), that tests and fails to reject the hypothesis that inflation and unemployment form a cointegrating relation, as implied by the Barro and Gordon model when the natural unemployment rate is non-stationary. Ruge-Murcia (2003) estimates a model that allows for asymmetric preferences, nesting the Barro and Gordon specification as a special case, and fails to reject the model of discretionary optimal monetary policy. Both these papers assume one equilibrium concept (discretion), and test whether some time series implications of discretionary policies, are rejected or not by the data.…”
Section: Introductionmentioning
confidence: 99%